Pendampingan Program Farkom (Farmakology and Complementary Therapy) Untuk Pasien dan Keluarga Penderita Kanker Payudara - Indah Sri Wahyuningsih; Fitria Endah Janitra; Asih Puji Lestari (University of Islam Malang, 2020)
Breast cancer patients need to get palliative care to improve their quality of life. Family existence becomes an important role for breast cancer sufferers to fulfill physical and psychological health. Palliative care can be given to patients in the form of complementary and pharmacological therapy (FARKOM). FARKOM's community service program aims to improve family knowledge and abilities in the care of family members with breast cancer and support for taking medication control. The target of this community service activity is to involve five families with breast cancer members in the Bandarharjo Village. The methods of this activity include lectures on the Farkom program (Pharmacology and complementary therapy), demonstrations of progressive muscle relaxation techniques and how to make beetroot juice, simulations by grouping participants according to family members and practicing, then monitoring and evaluating related to the Farkom program. Based on the pre-test and post-test results after being given treatment, there was an increase in the percentage value, namely a 25% increase in progressive muscle relaxation exercises, herbal juice production increased 30% and monitor filling schedule for taking medication increased 30%. Thus, this mentoring activity can be said to be successful because it can increase the knowledge and ability of participants in participating in community service activities.